Let a 0 , a 1 , ⋯ be a sequence defined by a 0 = 7 , a 1 = 8 , and, for all n ≥ 2 , a n = 5 a n − 1 − 6 a n − 2 Find the remainder when a 2 0 1 4 is divided by 1000.
See here for information regarding recurrence relations.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If I remember correctly, Euler's Theorem states that, a ϕ ( n ) ≡ 1 ( m o d n ) , if g cd ( a , n ) = 1 ∧ a , n ∈ Z +
So, using Euler's theorem with a = 3 , n = 1 0 0 0 works since g cd ( 3 , 1 0 0 0 ) = 1 , but how can we use it for a = 2 , n = 1 0 0 0 when g cd ( 2 , 1 0 0 0 ) = 2 = 1 ?
Correct me if I'm wrong. Thanks in advance. :)
Log in to reply
Your critique is correct.
He was lucky that the calculations work out. This happens because 1 4 > 3 and 2 3 ∣ ∣ 1 0 0 0 . As you were hinting, the right way to do this is 2 2 0 1 4 ≡ 0 ( m o d 8 ) and 2 2 0 1 4 ≡ 2 1 4 ( m o d 1 2 5 ) . Combining that gives us 2 2 0 1 4 ≡ 2 1 4 ( m o d 1 2 5 ) by CRT. Note that 2 2 0 0 1 ≡ 2 1 ( m o d 1 0 0 0 ) .
Problem Loading...
Note Loading...
Set Loading...
The characteristic polynomial is x 2 − 5 x + 6 = ( x − 2 ) ( x − 3 ) so the closed-form looks like a n = c 1 ( 2 n ) + c 2 ( 3 n ) Using the initial values, c 1 + c 2 = 7 2 c 1 + 3 c 2 = 8 Solving, c 1 = 1 3 and c 2 = − 6 . Thus, a n = 1 3 ( 2 n ) − 6 ( 3 n ) With n = 2 0 1 4 and modulo 1000, 1 3 ( 2 2 0 1 4 ) − 6 ( 3 2 0 1 4 ) ≡ 1 3 ( 2 1 4 ) − 6 ( 3 1 4 ) ( m o d 1 0 0 0 ) ≡ 1 3 ( 3 8 4 ) − 6 ( 9 6 9 ) ( m o d 1 0 0 0 ) ≡ 1 7 8 ( m o d 1 0 0 0 ) where the first step follows from Euler's totient theorem ( a 4 0 0 ≡ 1 ( m o d 1 0 0 0 ) ) and the second step follows from expanding out the powers.